1998
DOI: 10.1002/(sici)1521-186x(1998)19:3<140::aid-bem2>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Alternate indices of electric and magnetic field exposures among Ontario electrical utility workers

Abstract: Epidemiologic studies examining the risk of cancer among occupational groups exposed to electric fields (EF) and or magnetic fields (MF) have relied on traditional summaries of exposure such as the time weighted arithmetic or geometric mean exposure. Findings from animal and cellular studies support the consideration of alternative measures of exposure capable of capturing threshold and intermittent measures of field strength. The main objective of this study was to identify a series of suitable exposure metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…The relation between NHL and the cumulative TWA based on the geometric and arithmetic mean exposure in this study population has previously been reported 8. However, recent analyses to correlate the exposure data indicated that the use of the arithmetic and geometric means, by themselves, does not adequately characterise the variability of exposures to either electric or magnetic fields 42. The correlation analysis also suggested that alternate indices of exposure—such as the SD of field strength, the percentage of time above a threshold, and fluctuations of field strength over successive time intervals—should be evaluated when examining the relations between field exposure and cancer within this study population.…”
mentioning
confidence: 68%
“…The relation between NHL and the cumulative TWA based on the geometric and arithmetic mean exposure in this study population has previously been reported 8. However, recent analyses to correlate the exposure data indicated that the use of the arithmetic and geometric means, by themselves, does not adequately characterise the variability of exposures to either electric or magnetic fields 42. The correlation analysis also suggested that alternate indices of exposure—such as the SD of field strength, the percentage of time above a threshold, and fluctuations of field strength over successive time intervals—should be evaluated when examining the relations between field exposure and cancer within this study population.…”
mentioning
confidence: 68%
“…Multivariable statistical techniques9397 may also be useful in analysing multiple exposure metrics obtained by using measurement data from vector waveform monitors 9799…”
Section: Challengesmentioning
confidence: 99%
“…23 Assignment of exposure to magnetic fields Workers in the electric utility industry have complicated patterns of exposure to EMFs, with several possible measurements, including transient measures of magnetic and electric fields. 24,25 Exposure to EMFs was estimated by an assessment of exposure to magnetic fields, focusing on the time-weighted average, as described in detail elsewhere and briefly summarized here. 19,[26][27][28] Complete work histories were abstracted and computerized.…”
mentioning
confidence: 99%